Reciclagem e caracterização de fibra de carbono presente em compósito de resina epóxi - Rodrigues, Gleice Guevara Matielli (2013)
Carbon fiber reinforced epoxy composites are engineering materials whose are used in a wide range of applications in industries such as automotive, aerospace and sporting goods due to the properties of these composites as strength, durability, low weight and low cost. There are in the literature studies of various methods of recycling carbon fiber at the end of life from parts made with this material. This work reports a study of the polyacrylonitrile carbon fiber reinforced polymer recycling from diglicicil epoxy ether of bisphenol A composite. Initial studies were aimed at finding the best condition to remove the polymer matrix and thereby recover the carbon fiber by heat treatment in a muffle furnace. The matrix was removed at 450°C without degradation of the carbon fiber at 2 hours. The removal of the meanly volatile substances was verified with the Gas Chromatography analysis. The carbon fiber was incorporated randomly in the polyurethane matrix without chemical pre-treatment. The confirmation of the removal of the resin carbon fiber was obtained through the Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The characterization of the carbon fiber reinforced polyurethane composite was performed using the techniques: Thermogravimetric Analysis (TGA), Dynamic Mechanical Analysis (DMA) and FTIR. Thus, it was observed that the carbon fiber reinforced polyurethane at 2 % and 3% showed improvement in the mechanical properties since the storage modulus value was 3 and 4 times more than pure PU, respectively. Moreover, the glass transition temperature was more than 140°C for the composite polyurethane/carbon fiber and 110°C for the PU pure.